Marital status as an independent prognostic factor for patients of malignant pleural mesothelioma - Pan, Shu; Yan, Na; Zhao, Yuanyuan; Li, Zhiwen (Frontiers in Medicine, 2022)
Abstract Objectives: The prognostic impact of marital status on malignant pleural mesothelioma (MPM) is not investigated. This paper probes into the relation between prognosis of MPM and marital status. Methods: The Surveillance, Epidemiology, and End Results (SEER) database of American had been applied to choose eligible patients over the 2004-2015 periods. Moreover, Cancer-Specific Survival (CSS) and Overall Survival (OS) of unmarried and married groups were compared. Results: 3997 patients in total had been identified, including 2735 (68.43%) married patients. In comparison to unmarried patients, married ones tended to be younger, male, white and received active treatment (surgery, chemotherapy or radiotherapy). In addition, the 1, 3, 5-year CSS rates were 44.40%,12.09% and 6.88% in married patients, while 35.75%, 12.12% and 6.37% in unmarried group (P = 0.0014). At the same time, the 1, 3, 5-year OS rates were 41.84%,10.56% and 5.91% in married patients, while 33.67%, 10.44% and 4.93% respectively in unmarried group (P < 0.0001). As revealed by the multivariate analysis results, the marital status was an independent favorable prognostic factor, in which the married groups showed better CSS [hazard ratio (HR): 0.870; 95% confidence interval (CI): 0.808–0.938; P<0.001] as well as OS (HR: 0.871; 95%CI: 0.810–0.936; P<0.001). According to the results of subgroup analysis, the CSS and OS survival of married groups were better than the unmarried groups in almost all the subgroups. Conclusion: Marital status is an independent favorable prognostic indicator of MPM. Poor prognosis in unmarried patients is likely to be related to insufficient treatments, socioeconomic and psychosocial factors.